Learning Needs, Expectations and Views of General Surgery Patients. - Savcı, Cemile; Karaaslan, Yurdanur; Yüksel, Serpil (Journal of Academic Research in Nursing (JAREN), 2021)
Objective: This study was planned to determine the learning needs and expectations of general surgery patients and their views on the education provided. Method: 145 patients hospitalized in the general surgery clinic of a training and research hospital between December 2014-February 2015 constituted the population of this descriptive and crosssectional study. The sample of the study consisted of 105 patients who met the inclusion criteria with a sampling error of 0.05. The "Personal Information Form" consisting of 12 questions and the "Patient Learning Needs Scale (PLNS)" were used as the data collection tools. Data analysis was performed in SPPS 20 (IBM Corp. Released 2011, Armonk, NY: IBM Corp.) statistical program with descriptive analysis, independent samples t-test, one-way analysis of variance and advanced analyses. Results: In the study in which 52.4% of the participants were over the age of 50 and 55.2% of them were female, the majority indicated that the most effective education methods were verbal expression (51.4%) and practical expression (50.5%). It was determined that 60% and all of the participants wanted to be educated and informed before admission to the hospital and at discharge, respectively. According to the mean total PLNS score (208.39±12.50), it was determined that the learning needs of the patients were high. When the subscale scores of the scale were evaluated, it was determined that the patients had higher learning needs in the dimensions of "treatment and complications" (39.09±2.43), "activities of living" (36.01±3.91), "medications" (34.66±2.54), however, the dimension with the lowest learning needs was "feelings related to condition" (19.12±1.92). Conclusion: The results of the study indicated that surgical patients had high learning needs before discharge. Accurate diagnosis of patients' learning needs and expectations is important since it will increase the quality and effectiveness of discharge education.